Time Courses of Inflammatory Markers after Aneurysmal Subarachnoid Hemorrhage and Their Possible Relevance for Future Studies - Höllig, Anke; Stoffel-Wagner, Birgit; Clusmann, Hans; Veldeman, Michael; Schubert, Gerrit A.; Coburn, Mark (Frontiers in Neurology, 2017)
Object: Aneurysmal subarachnoid hemorrhage triggers an intense inflammatory response, which is suspected to increase the risk for secondary complications such as delayed cerebral ischemia (DCI). However, to date, the monitoring of the inflammatory response in order to detect secondary complications such as DCI has not become part of the clinical routine diagnostic. Here, we aim to illustrate the time courses of inflammatory parameters after aSAH and discuss the problems of inflammatory parameters as biomarkers but also their possible relevance for deeper understanding of the pathophysiology after aSAH and sophisticated planning of future studies. Material and Methods: In this prospective cohort study 109 patients with aSAH were initially included, n = 28 patients had to be excluded. Serum and –if possible- cerebral spinal fluid (CFS) samples (n = 48) were retrieved at day 1, 4, 7, 10 and 14 after aSAH. Samples were analyzed for leukocyte count and C-reactive protein (serum samples only) as well as matrix metallopeptidase 9 (MMP9), intercellular adhesion molecule 1 (ICAM1) and leukemia inhibitory factor (LIF) (both serum and CSF samples). Time courses of the inflammatory parameters were displayed and related to the occurrence of DCI. Results: We illustrate the time courses of leukocyte count, CRP, MMP9, ICAM1 and LIF in patients´ serum samples from the first until the 14th day after aSAH. Time courses of MMP9, ICAM1 and LIF in CSF samples are demonstrated. Further, no significant difference was shown relating the time courses to the occurrence of DCI. Conclusions: We estimate that the wide range of the measured values hampers their interpretation and usage as a biomarker. However, understanding the inflammatory response after aSAH and generating a multicenter database may facilitate further studies: Realistic sample size calculations on the basis of a multicenter database will increase the quality and clinical relevance of the acquired results.